Taxonomic status of Strobilanthes warreensis (Acanthaceae), an endemic species of Western Ghats, India - Mascarenhas, Maria Emilia; Janarthanam, M. K. (Rheedea, 2013)
Strobilanthes warreensis Dalzell (Acanthaceae) is endemic to the Western Ghats. Due to its close resemblance to S. ciliatus Nees, it has been critically studied along with the latter and evaluated for its taxonomic status and circumscription. Based on our studies, including that of type and tagged live specimens in the field, it is concluded that both are conspecific. Therefore, S. warreensis has been synonimised here under S. ciliatus.